Increase in Production Capacity of Stirred Yogurt Using Konjac Glucomannan Stabilizer at UKM Sehati Purwokerto: Peningkatan Kapasitas Produksi Stirred Yogurt Menggunakan Stabilizer Konjac Glucomannan di UKM Sehati Purwokerto - Hamad, Alwani; Haryanto, Totok; Mulyadi, Abdul Haris; Hasanah, Yeti Rusmiati; Magribi, Imam Maulana (Yayasan Ahmar Cendekia Indonesia, 2024)
UKM Sehati Yogurt Purwokerto produces good-quality yogurt but faces challenges in product stability, shelf life, and market competitiveness. To address these issues, product diversification using a konjac glucomannan stabilizer is proposed to align with consumer trends. However, marketing also presents a significant obstacle. This community service program aims to transfer yogurt production technology using konjac stabilizer and offer digital marketing guidance to enhance market reach. The program involves two steps: technology transfer and marketing support. The technology transfer includes training for the UKM owner and community on using the Konjac glucomannan stabilizer in stirred yogurt production. The digital marketing support involves providing training on creating promotional content for social media and utilizing online marketplaces for sales. The outcomes of this program include the successful production of new, higher-quality yogurt products with the added health benefits of konjac fiber. Additionally, the UKM owner and community gained new skills in both production and digital marketing. After the digital marketing training, the SME actively engaged in online sales, broadening its consumer reach. This initiative is expected to increase sales significantly through product diversification and expanded digital marketing efforts.